Prevalence and Predictors of Tobacco Use Among School Adolescents in Zakho, Kurdistan Region of Iraq - Kachel, Hamid S.; Ageed, Mohammed A.; Omer, Nergiz H.; Suleiman, Mohammed I. (Science Journal of University of Zakho, 2018)
Knowledge regarding the smoking prevalence among the Kurdistan general population is not clear, at least for males. Here in the Kurdistan Youth Smoking Survey and Behaviours (KYSS&B) we tried to further expand our knowledge about the smoking profile of school students across Kurdistan. Five hundred students from four Zakho male basic schools were taken to participate in the study to determine the prevalence of smoking and socio-demographical factors associating with smoking among students aged 12 to 15 years. The KYSS&B questionnaire included various parameters such as age, gender, friends, parent history and blood groups. This study showed that the prevalence of students who ever tried smoking was 74%; about 65% of them started at age 12 years or less. Although the majority of participants (95%) knew that smoking is harmful and had negative impact on human health, 18% of them thought that they will never quit smoking. The study concluded that there was no strong association between family monthly income, parent education level and blood groups. On the other hand, the three most critical factors connected with smoking habit reported by students were age, peer influence and father smoking.